2024
DOI: 10.3390/children11010092
|View full text |Cite
|
Sign up to set email alerts
|

Ponte Osteotomies in the Surgical Treatment of Adolescent Idiopathic Scoliosis: A Systematic Review of the Literature and Meta-Analysis of Comparative Studies

Cesare Faldini,
Giovanni Viroli,
Matteo Traversari
et al.

Abstract: The purpose of the present paper is to assess if Ponte osteotomies (POs) allow for a better correction in adolescent idiopathic scoliosis (AIS) surgery and to investigate their safety profile. A systematic search of electronic databases was conducted. Inclusion criteria: comparative studies that reported the outcomes of AIS patients who underwent surgical correction through posterior-only approach with and without POs. Clinical and radiographic outcomes were extracted and summarized. Meta-analyses were perform… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 37 publications
0
3
0
Order By: Relevance
“…Therefore, a stronger fixation secondary to larger diameter screws increases the corrective forces applied to the deformed spine in all three planes, allowing for increased correction in all three dimensions. However, recent studies have shown that POs may have little to no impact on the sagittal plane and may be associated with neuromonitoring complications, higher costs, and risk of readmission, without a benefit in patient-reported outcomes [34][35][36].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Therefore, a stronger fixation secondary to larger diameter screws increases the corrective forces applied to the deformed spine in all three planes, allowing for increased correction in all three dimensions. However, recent studies have shown that POs may have little to no impact on the sagittal plane and may be associated with neuromonitoring complications, higher costs, and risk of readmission, without a benefit in patient-reported outcomes [34][35][36].…”
Section: Discussionmentioning
confidence: 99%
“…This higher kyphosis can be explained by the increased fixation strength of largerdiameter screws, which can maintain the contoured rod bend and thoracic curvature during rotation [34,36,57]. Matsukawa et al conducted a finite element analysis comparing the influence of the segmental screw diameter, length, and fill on construction in osteoporotic vertebrae and found that an increased screw diameter was significantly more resistant to vertebral flexion-extension loading [50].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation